HETEROGENEITY OF HAEMOPHILIA A GENETIC AND ENVIRONMENTAL FACTORS ON THE DEVELOPMENT OF FACTOR VIII INHIBITORS - Roswati MN (Asian Journal of Medicine & Health Sciences, 2020)
Haemophilia A (HA) is a rare disease by definition, as it affects 1 in 5,000 male livebirths, but it is the commonest among inherited bleeding disorders. There are 1,295 HA cases registered in hospitals under Ministry of Health (MOH) for Factor VIII (FVIII) replacement therapy and 83 (6.4%) are identified to have FVIII allo-antibodies or inhibitors, which is an under-reported figure as studies have shown that 30% of HA develop inhibitors. With the recent adoption of prophylactic FVIII replacement therapy, this treatment modality will greatly improve the quality of life for HA. Unfortunately, 30% of HA develop inhibitors and this causes management of HA with inhibitors very challenging with progressive arthropathy, disability and increase in treatment costs. There have been many studies on mechanisms of inhibitor development, but the pathogenesis is not being fully elucidated. Risk factors to inhibitor development are grouped into genetic or non-modifiable and environmental risk factors. FVIII gene mutation has been consistently identified to be the most important risk factor. This review paper discusses on the genetics and environmental risk factors on inhibitor development in HA, towards better understanding in predicting which HA have the highest risk and lowest risk of inhibitor development and strategized appropriate treatment modality.